The Influence Of Indonesian Elderly Fitness Fit (SBLI) On The Reduction Of Cholesterol Levels On The Elderly: Literature Review - MARSHA KOMUL (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2022)
ABSTRACTProblem Statement : An increase in blood cholesterol levels is one of the triggers for stroke and coronary heart disease which is the biggest cause of death in Indonesia. For those who have high cholesterol levels, exercise and diet are the main keys to lowering cholesterol levels. One type of exercise that can reduce blood cholesterol levels is the Indonesian Elderly Fitness Gymnastics (SBLI) so that it does not affect heart function. Methods : This study uses a literature review by comparing related research journals that have been published by at least 10 journals to determine the effect of fitness exercise for the elderly in Indonesia (SBLI) on the reduction of cholesterol levels in the elderly. In this study, the initial journal literature was collected as many as 12 journal literatures and then filtered 7 journal literature in accordance with related research and then conducted a review. Search strategy for research articles using Google Scholar, Jurnal Kesehatan Kusuma Husada, Jurnal Ilmu Kedokteran dan Kesehatan, URECOL, Jurnal Biomedik (JBM), Digilib Unnes, Jurnal Sistem Kesehatan, Jurnal e-Biomedik (eBM), e-journal Undiksha, Institutional Repository UNS, Jurnal Keperawatan Respati Yogyakarta and Semantic Scholar. The keywords used are cholesterol, the elderly and fitness gymnastics for the Indonesian elderly. Inclusion criteria include articles indexed nationally and internationally, publication year 2009-2019, original research, full text. The exclusion criterion is if the research design uses a qualitative design. The articles obtained were as many as 7 journal literature, analyzed in table format containing the researcher, research subject, year, measuring instrument, measurement results, research results, and comparison with proposed research. Results : A total of 12 preliminary journal literatures were collected and then filtered 7 journal literature according to related research and has the effect of reducing blood cholesterol levels. This shows that there is an effect of Gymnastics for the Indonesian Elderly (SBLI) on blood cholesterol levels in the elderly. Conclusion : Indonesian Elderly Gymnastics Fitness (SBLI) is able to reduce blood cholesterol levels in the elderly.